Lenka Jakoubková Budilová – Thomas Hylland Eriksen – Gunnar Haaland – Miroslav Hroch – Marek Jakoubek: Etnické skupiny, hranice a identity - Krupková, Kateřina (Lidé města, 2022)
A review of the book by Lenka Jakoubková Budilová, Thomas Hylland Eriksen, Gunnar Haaland, Miroslav Hroch and Marek Jakoubek.